2021
DOI: 10.1002/nafm.10701
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variability of Fishery‐Dependent Indices for the Declining Louisiana Southern Flounder Fishery

Abstract: In recent years, management agencies across the Gulf of Mexico and southern U.S. Atlantic have recognized Southern Flounder Paralichthys lethostigma as a declining fish stock. Population declines in coastal Louisiana are exhibited by indices of recruitment and biomass, which have reached levels that present management concerns. To develop a better understanding of this declining fishery, we examined fishery-dependent data collected by the Louisiana Department of Wildlife and Fisheries' recreational angler harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Additionally, over half of respondents (57.3%) indicated that they did not know whether the Southern Flounder fishery has changed or stayed the same over the past 5 years. With the current abundance of Louisiana Southern Flounder at relatively low levels when compared to historic values (West et al 2020) and the amount of harvest within the recreational fishery declining in recent years (Smith et al 2021a), the decline over the past 5 years would seemingly be apparent for those targeting Southern Flounder. That this decline has gone unnoticed is likely due to the incidental nature of Southern Flounder targeting behaviors in coastal Louisiana.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, over half of respondents (57.3%) indicated that they did not know whether the Southern Flounder fishery has changed or stayed the same over the past 5 years. With the current abundance of Louisiana Southern Flounder at relatively low levels when compared to historic values (West et al 2020) and the amount of harvest within the recreational fishery declining in recent years (Smith et al 2021a), the decline over the past 5 years would seemingly be apparent for those targeting Southern Flounder. That this decline has gone unnoticed is likely due to the incidental nature of Southern Flounder targeting behaviors in coastal Louisiana.…”
Section: Resultsmentioning
confidence: 99%
“…2020) and the amount of harvest within the recreational fishery declining in recent years (Smith et al. 2021a), the decline over the past 5 years would seemingly be apparent for those targeting Southern Flounder. That this decline has gone unnoticed is likely due to the incidental nature of Southern Flounder targeting behaviors in coastal Louisiana.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Southern Flounder ( Paralichthys lethostigma ) are an estuarine-dependent species best known for their late fall spawning migrations (October-December) and are among the most targeted fish in Texas marine waters [ 1 – 4 ]. Historically, Southern Flounder have supported an important multimillion-dollar commercial and recreational fishery along the Texas coast and the broader Gulf of Mexico (Gulf) [ 5 , 6 ]; however, the Gulf’s, especially Texas’, Southern Flounder populations have been in steady decline since the 1980s prompting numerous management revisions aimed at reducing harvest and effort in the fishery [ 7 9 ]. Despite these regulatory changes, Southern Flounder have continued to experience an overall decline [ 8 , 10 , 11 ].…”
Section: —Introductionmentioning
confidence: 99%